The Use of Graphing Calculators in Teaching Mathematics: A Meta-Synthesis - Angco, Robert Jay; Aliser, Alger; Lacson, Emy; Bonotan, Amelia (Jurnal Pendidikan Progresif, 2023)
The Use of Graphing Calculators in Teaching Mathematics: A Meta-Synthesis. Objectives: This study aimed to explore the use of graphing calculators as a tool in teaching and learning mathematics employing a meta-synthesis method. Methods: A meta-synthesis was used in this study. The final 16 articles used in this study were the result in using the Critical Appraisal Skills Programme (CASP) checklist and the PRISMA 2020 flow diagram. Findings: Six themes emerged from the data: (1) influences students' solving and basic skills; (2) the need for complex technical skills; (3) readiness in learning mathematics; (4) facilitative role of the teachers; (5) excellent aid for better comprehension and representation; and (6) increases students' cognitive achievement. The study's meta-theme emerged as the “exploration and navigation on the use of the graphing calculators.” Conclusion: The use of graphing calculators was found very useful in teaching mathematics. It is recommended that a training the use of the graphing calculator be given to both teachers and student; the offering of elective subjects which deal on the use of different technologies useful in Math teaching/learning be considered. Keywords: graphing calculators, meta-synthesis, systematic review, teaching mathematics.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202307